2015
DOI: 10.1080/10255842.2015.1042465
|View full text |Cite
|
Sign up to set email alerts
|

Improving anterior deltoid activity in a musculoskeletal shoulder model – an analysis of the torque-feasible space at the sternoclavicular joint

Abstract: Modelling the shoulder's musculature is challenging given its mechanical and geometric complexity. The use of the ideal fibre model to represent a muscle's line of action cannot always faithfully represent the mechanical effect of each muscle, leading to considerable differences between model-estimated and in vivo measured muscle activity. While the musculotendon force coordination problem has been extensively analysed in terms of the cost function, only few works have investigated the existence and sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
(87 reference statements)
2
4
0
Order By: Relevance
“…The associated results from the in vitro [17], in vivo [8,18,19,21], and numerical [10,[12][13][14] studies are also shown. present study, 6DOF present study, 3DOF Sins et al [12] Ingram et al [41] Bergman et al [43] Favre et al [14] Terrier et al [10] Quental et al [13] Nikooyan et al [5] Nikooyan et al [42] Figure 5: The GH joint contact force predicted by the present study and the associated results from numerical [5, 10, 12-14, 41, 42] and in vivo studies [43]. The results predicted by a similar GH joint model but with 3 DOF (ideal ball-and-socket) including the stability constraint is also shown.…”
Section: Resultssupporting
confidence: 50%
“…The associated results from the in vitro [17], in vivo [8,18,19,21], and numerical [10,[12][13][14] studies are also shown. present study, 6DOF present study, 3DOF Sins et al [12] Ingram et al [41] Bergman et al [43] Favre et al [14] Terrier et al [10] Quental et al [13] Nikooyan et al [5] Nikooyan et al [42] Figure 5: The GH joint contact force predicted by the present study and the associated results from numerical [5, 10, 12-14, 41, 42] and in vivo studies [43]. The results predicted by a similar GH joint model but with 3 DOF (ideal ball-and-socket) including the stability constraint is also shown.…”
Section: Resultssupporting
confidence: 50%
“…Combined with the force amplitude obtained by data driven methods such as that proposed in (Wang et al 2010) both amplitude and direction can be assessed. However, the FFS allows to explain such direction, give more general information on the whole force capabilities and can be used for a wide range of applications including ergonomic indices for wheelchair propulsion (Hernandez et al 2018), for modulating the assistance of rehabilitation robots (Carmichael and Dikai 2013) or for improving the design of musculoskeletal models (Ingram et al 2016) to name a few.…”
Section: Discussionmentioning
confidence: 99%
“…The model of the FFS has identified limitations. Indeed, a stability constraint should be added to control the direction of joint force at the glenohumeral joint (Ingram et al 2016). More muscles should be considered especially those of the thorax.…”
Section: Discussionmentioning
confidence: 99%
“…abduct, flex and internally rotate the humerus at the same time), it is important to describe all three corresponding moment arms components. While the tendon excursion method may seem easy to implement, it can be improperly used, particularly in the case of multiple degrees of freedom and muscles spanning more than one joint 14 . The geometric method involves measurement of the perpendicular distance between the muscle's line of action and the joint centre of rotation 15 and computes the three moment arms components.…”
Section: Introductionmentioning
confidence: 99%